Perlindungan Hukum Terhadap Kerahasiaan Data Pasien Antara Rekam Medis Konvensional Dan Elektronik - Tifany Dwi Harant (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Health service facilities have the duty and obligation to protect the confidentiality of information contained in medical record files and must not disclose or provide this information to unauthorized people or institutions. The aim of this research is to determine legal protection for the confidentiality of patient data between conventional and electronic medical records. The research method used is normative juridical. The research results show that legal protection can be grouped into two, namely preventive and repressive legal protection. Preventive legal protection or prevention of violations related to medical records can be carried out by maintaining the confidentiality of medical records, maintaining medical record storage, and maintaining procedures for the release of health information. Meanwhile, repressive legal protection can be carried out by taking responsibility for violations that have been committed in the form of criminal, civil and administrative sanctions.